MANAJEMEN ALUMNI SEBAGAI STRATEGI MARKETING PERGURUAN TINGGI - Muzaki, Hasan (Dinamika: Jurnal Manajemen Sosial Ekonomi, 2023)
For a university, alumni are the core product produced. One of the good and bad aspects of a college can be seen from the quality and quantity of its alumni. Alumni as one of the higher education stakeholders are expected to make a significant contribution to the university. This contribution can be in the form of financial contributions or other contributions such as as a promotional medium and a strong magnet for attracting new students. From this it can be seen that from various aspects alumni can make quite a large contribution to the development of higher education. Marketing strategy is a way for an institution to position itself so that its products can be of interest to consumers or potential consumers. Several things that universities can do regarding how to manage alumni as an effective and efficient marketing strategyL 1). Make alumni feel proud and have ownership of the university (2) Establish continuous communication. (3) Recruit alumni as part of the campus education staff, (4) Facilitate alumni in achieving their future. Harmonious cooperation and mutualism between alumni and universities will have a major impact on the sustainable development of universities from now until the future.